Wet metallization of 3D printed microarchitectures: Application to the manufacturing of bioinspired microswimmers. (June 2022) - Bernasconi, R.; Prioglio, G.; Angeli, M. Costa; Alcantara, C.C.J.; Sevim, S.; Pané, S.; Vena, P.; Magagnin, L.
Abstract: Untethered microswimmers have been recently proposed as possible candidates for a wealth of biomedical and environmental applications. In view of their translation from laboratory experimentation to clinical practice, it is fundamental to identify low-cost, scalable and flexible manufacturing approaches. The production method explored in the present paper, which responds to all these requirements, consists of a smart combination of two-photon lithography (2PL) and wet metallization. Fully functional bioinspired artificial bacterial flagella (ABFs) are successfully 3D printed following a user-defined model and made magnetically active by depositing a layer of CoNiP alloy on their surface via electroless deposition. In contrast with existing ABFs metallization approaches based on metal evaporation, electroless deposition does not suffer from the shadowing effect, and it can be employed to easily plate hard-magnetic alloys. The specific challenges of the application of electroless plating to the metallization of 2PL printed polymeric templates are identified, discussed and addressed. The manuscript also explores the possibility to impart multiple functionalities to the 3D printed microstructures by applying multiple metallic layers on their surface. Besides the applicative example of ABFs, the metallization methodology presented can be potentially used for the metallization of a great variety of 2PL printed microarchitectures for many possible applications. Graphical abstract: Unlabelled Image Highlights: Wet metallization and laser direct writing are combined to build microarchitectures. The challenges of the wet metallization of micrometric objects are identified. As applicative example, untethered artificial bacterial flagella are manufactured. CoNiP wet coated devices demonstrate controllable and efficient magnetic actuation. Silver is deposited on CoNiP to demonstrate the possibility to apply multilayers.